Romanticism, enthusiasm, and regulation poetics and the policing of culture in the Romantic period - Mee, Jon (Oxford University Press, 2003)
This study looks at the way writers in the Romantic period, both canonical and popular, attempted to situate themselves in relation to enthusiasm, frequently craving the idea of its therapeutic power, but often also seeking to distinguish their writing from what many regarded as its destructive and pathological power.